Reading Animation as Pedagogical Strategy for Development of the Literary Competence in High School - Rojas Camargo, Derly Juliana (Universidad Pedagógica y Tecnológica de Colombia, 2018)
A continuous unanswered question has been asked in the literary and educational fields around literature didactics. Is it possible to teach how to read literature to teenagers? Literature teaching is a field that has been broached by experts who have worked with the mentioned population in the literary reading. According to this, the purpose of this article is to make a brief reflection around literary education, besides, its aim is to offer feasible answers in relation to an important subject in the school through the reception theory, which, it seems to be, the most suitable one in literature teaching, as it gives preference to the aesthetic experience of the reader with the literary text.